Syntheses and Fundamental Properties of Cr/Mo-Adoped Fe-Rich Alloys With Metastable Phase and Saturation Magnetization Near 1.9 T - Ding,Jian (2016)
The Fe-rich alloys of Fe90-xSi5B5Mx (M= Cr or Mo; x=1, 2) are synthesized in the present study. The as-spun structure mainly consists of bcc phase plus a minor amount of metastable phase (Fe3B and/or Fe23B6). Comparing with the base alloy Fe90Si5B5, the corrosion resistance is improved significantly due to the formation of the passive film. Saturation magnetic flux density reaches 1.9 T for the melt-spun alloys Fe89Mo1Si5B5. The alloys present a nearly constant high permeability in a rather high magnetic field up to coercive field which can be used as a new kind of sensor material with good fundamental properties and low cost.